2019
DOI: 10.1111/his.13796
|View full text |Cite
|
Sign up to set email alerts
|

Somatic genetic alterations in synchronous and metachronous low‐grade serous tumours and high‐grade carcinomas of the adnexa

Abstract: Aims Low‐grade serous carcinomas (LGSCs) and their precursors serous borderline tumours (SBTs) characteristically harbour mutations in BRAF, KRAS or NRAS but rarely in TP53, whereas high‐grade serous carcinomas (HGSCs) are characterised by frequent TP53 mutations but rare BRAF, KRAS or NRAS mutations. In a small subset of cases, LGSCs and/or SBTs develop into high‐grade tumours, including HGSCs and poorly differentiated carcinomas (PDCs). Here, we sought to define the repertoire of somatic genetic alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Clonal composition analysis revealed that primary aGCTs and their matched recurrences, despite their generally simple genomes with few mutations and copy number alterations, display intra-lesion heterogeneity harboring clonal and subclonal mutations. In the progression from primary to metastatic disease, the acquisition of additional mutations, loss of heterozygosity of the wild-type allele of a given mutated gene as well as clonal shifts of genes affected by somatic mutations have been described [49][50][51]. Through the analysis of paired primary and matched recurrent aGCTs, we found that the acquisition of mutations, including those affecting TP53, TET2, MED12 and SH2D1A, was most commonly associated with disease progression.…”
Section: Discussionmentioning
confidence: 86%
“…Clonal composition analysis revealed that primary aGCTs and their matched recurrences, despite their generally simple genomes with few mutations and copy number alterations, display intra-lesion heterogeneity harboring clonal and subclonal mutations. In the progression from primary to metastatic disease, the acquisition of additional mutations, loss of heterozygosity of the wild-type allele of a given mutated gene as well as clonal shifts of genes affected by somatic mutations have been described [49][50][51]. Through the analysis of paired primary and matched recurrent aGCTs, we found that the acquisition of mutations, including those affecting TP53, TET2, MED12 and SH2D1A, was most commonly associated with disease progression.…”
Section: Discussionmentioning
confidence: 86%
“…Yet, all four samples with sequencing data from this patient showed LOH on the whole chromosome 17 and a clonal TP53 mutation in addition to NRAS . Cases with such genomic and morphological features from both high and low-grade serous carcinomas have previously been reported as rare variants of serous ovarian neoplasms [20, 37]. A further study on the potential origin and genomic and histological evolution of this and the two BRAF -mutated HGSC cases discovered through exploration in GenomeSpy is ongoing.…”
Section: Resultsmentioning
confidence: 99%
“…Although the vast majority of extrauterine classic high-grade serous carcinomas originate from STIC, a small subset of ovarian high-grade carcinomas (which are probably variably diagnosed as highgrade serous carcinoma in routine practice) represent high-grade transformation of ovarian serous borderline tumours/low-grade serous carcinomas. [108][109][110][111][112][113] While morphology alone is by no means perfect in diagnosing STIC, the added use of immunohistochemistry for p53 and Ki-67 to supplement the histological features will help to establish a more reliable diagnosis. Molecular classification of tubal lesions, including reactive tubal epithelium, p53 signature and STIC, represents an unmet need to refine STIC diagnosis beyond histology.…”
Section: Discussionmentioning
confidence: 99%
“…Much has been learned during the last several years regarding the identification of STIC and its important roles in the development of invasive high‐grade serous carcinomas of the ovary, fallopian tube and peritoneum. Although the vast majority of extrauterine classic high‐grade serous carcinomas originate from STIC, a small subset of ovarian high‐grade carcinomas (which are probably variably diagnosed as high‐grade serous carcinoma in routine practice) represent high‐grade transformation of ovarian serous borderline tumours/low‐grade serous carcinomas 108–113 . While morphology alone is by no means perfect in diagnosing STIC, the added use of immunohistochemistry for p53 and Ki‐67 to supplement the histological features will help to establish a more reliable diagnosis.…”
Section: Discussionmentioning
confidence: 99%